Conceptualizing the Subanen Customary Legal System: An Ethnographic Typology of an Indigenous Legal Order in the Philippines - Dirb Boy O. Sebrero (Journal of Daoist Studies, 2026)
Indigenous customary laws remain vital systems of governance that regulate social relationships, resource management, and cultural continuity within Indigenous communities. However, existing scholarship has largely documented customary practices without adequately conceptualizing how they function as integrated Indigenous legal systems. This study examined the customary laws of the Subanen community in one of the municipalities of Zamboanga del Sur, Philippines, to develop an empirically grounded understanding of the Subanen customary legal system. Employing a qualitative ethnographic design, the study involved fifteen purposively selected participants, comprising eleven community elders, two tribal leaders, one Timuay, and one Indigenous Peoples Mandatory Representative (IPMR). Data were generated through community immersion, participant observation, and semi-structured key informant interviews, and analyzed using Braun and Clarke's Reflexive Thematic Analysis within an ethnographic framework. The findings revealed that the Subanen customary legal system operates through four interdependent domains of governance: Relational Governance, Continuity Governance, Territorial Governance, and Cosmological Governance. Collectively, these domains constitute a preventive Indigenous legal order that establishes reciprocal obligations, reinforces communal accountability, and preserves social harmony before disputes arise. Building on these findings, the study proposes a Typology of the Subanen Customary Legal System, offering a conceptual framework that advances scholarship on Indigenous Legal Orders, legal anthropology, and legal pluralism by demonstrating how customary law functions as an integrated system of governance embedded in the social, territorial, and spiritual life of the community.